Daphnetin modulates GLP-1R to alleviate cognitive dysfunction in diabetes: implications for inflammation and oxidative stress - Liang, Feng; Tian, Xinyi; Ding, Lining (Frontiers in Pharmacology, 2024)
Daphnetin exerts certain pharmacological function on a variety of diseases, but its role in diabetic cognitive dysfunction has not been elucidated. In this study, we carried a series of pharmacological studies of GLP-1R with daphnetin. In rats and PC12 cells, we found that daphnetin could alleviate diabetic cognitive dysfunction and increase the expression level of GLP-1R.Additionally, the anti-diabetic cognitive dysfunction effect of DAP was accompanied by the inhibition of inflammation and oxidative stress. Further in-depth studies demonstrated that the inhibition GLP-1R enhanced the protective effect of daphnetin, whilst, the overexpression of GLP-1R weakened the protective effect of daphnetin. These results indicated that daphnetin protects diabetes cognitive dysfunction by regulating GLP-1R-mediated inflammation and oxidative stress, act as a GLP-1R agonist. The study further demonstrated that daphnetin has great value in preventing cognitive dysfunction in type 2 diabetes, and GLP-1R is a key potential target for the treatment of related diseases.